Out-of-plane behaviour of a full scale stone masonry facade. Part 1: specimen and ground motion selection - Alexandre A. Costa (2013)
The out-of-plane response of walls in existing stone masonry buildings is one of the major causes of vulnerability commonly observed in post-earthquake damage surveys. In this context, a shaking table (ST) test campaign was carried out on a full-scale masonry facade mainly focusing on the characterization of its out-of-plane overturning behaviour. The structure tested on the ST is a partial reproduction of an existing building from Azores, damaged during the 9 July 1998 Faial earthquake. The definition of the tested specimen as well as the selection of the input ground motion is reported in this paper. A specific emphasis is given to the definition of the time-history to be applied during the tests because it was felt as an essential and crucial part of the work to obtain the desired overturning behaviour. The accelerogram to be imposed was selected from a large set of accelerograms (74) by means of a step-by-step procedure on the basis of several numerical analyses resorting to the rocking response of rigid blocks. A companion paper (Part 2) focuses on the ST test results and detailed data interpretation. Copyright (c) 2013 John Wiley & Sons, Ltd.